Impact of SnF2 Addition on the Chemical and Electronic Surface Structure of CsSnBr3 - Hartmann, Claudia; Gupta, Satyajit; Bendikov, Tatyana; Kozina, Xeniya; Kunze, Thomas; Félix, Roberto; Hodes, Gary; Wilks, Regan G.; Cahen, David; Bär, Marcus (ACS Applied Materials and Interfaces, 2020)
We report on the chemical and electronic structure of cesium tin bromide (CsSnBr3) and how it is impacted by the addition of 20 mol % tin fluoride (SnF2) to the precursor solution, using both surface-sensitive lab-based soft X-ray photoelectron spectroscopy (XPS) and near-surface bulk-sensitive synchrotron-based hard XPS (HAXPES). To determine the reproducibility and reliability of conclusions, several (nominally identically prepared) sample sets were investigated. The effects of deposition reproducibility, handling, and transport are found to cause significant changes in the measured properties of the films. Variations in the HAXPES-derived compositions between individual sample sets were observed, but in general, they confirm that the addition of 20 mol % SnF2 improves coverage of the titanium dioxide substrate by CsSnBr3 and decreases the oxidation of SnII to SnIV while also suppressing formation of secondary Br and Cs species. Furthermore, the (surface) composition is found to be Cs-deficient and Sn-rich compared to the nominal stoichiometry. The valence band (VB) shows a SnF2-induced redistribution of Sn 5s-derived density of states, reflecting the changing SnII/SnIV ratio. Notwithstanding some variability in the data, we conclude that SnF2 addition decreases the energy difference between the VB maximum of CsSnBr3 and the Fermi level, which we explain by defect chemistry considerations.
CRIS-Team Scopus Importer:2020-03-27
Keywords: chemical composition; CsSnBr3; impact of SnF2; perovskites; photoemission; thin-film solar cells